Caregiving : technology and livelihood education : modules in home economics - Gabriel, Oscar S., Jr. (Quezon City : St. Bernadette Publishing House Corporation., 2015)
"Caregiving pertains to the assistance of a caregiver to a patient who is ill, disabled, or in need of special attention". the caregiver has a great part in physical, mental, emotional, and psychological well being of the person being care of. it is important for the caregiver to be equipped with the knowledge that will direct behaviors for priority-setting, decision-making, and a problem-solving skills. He/she should be capable of using information, direct care strategies, coaching, and emotional support to work well with the care recipient".
Includes bibliographical references.
English text.
Keywords: Caregivers